2016
DOI: 10.1177/0032258x16662684
|View full text |Cite
|
Sign up to set email alerts
|

Organisational justice’s relationship with job satisfaction and organisational commitment among Indian police

Abstract: The concept of justice plays an important role in shaping the attitudes of citizens towards criminal justice agencies. Additionally, research indicates that police officers' perceptions of justice within their own organisation can affect their attitudes towards it. Most of the research to date has focused on police officers in Western nations; however, the effects of organisational justice could be universal (i.e. cut across different police agencies and nations) or contextual (i.e. vary between cultures). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 70 publications
6
99
0
1
Order By: Relevance
“…The Police Federation's commissioned surveys find staff noting increased workloads and greater stress burdens. Given that police research demonstrates relationships between organisational commitment, and the belief that one's organisation is a fair environment in which to work (Qureshi et al, 2017, Bradford et al, 2014, this is particularly relevant under conditions of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The Police Federation's commissioned surveys find staff noting increased workloads and greater stress burdens. Given that police research demonstrates relationships between organisational commitment, and the belief that one's organisation is a fair environment in which to work (Qureshi et al, 2017, Bradford et al, 2014, this is particularly relevant under conditions of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Equality implies that all employees are handled the same, regardless of their attempts or effect. Equity means that the result is determined by an individual worker's initiatives and input (Qureshi et al, 2017). Under the equity exchange principle, an individual assesses the organizational output based on inputs and compares these with the results of other workers in similar situations and what is considered as just (Greenberg, 1990).…”
Section: Djmentioning
confidence: 99%
“…PJ refers to how the results are allocated, not the results themselves. PJ Refers to the preconception that the systems and processes used by the organization to achieve remarkable results should be just and fair (Greenberg, 1982;Qureshi et al, 2017). Most employees want accurate, open and honest processes used to determine distribution results regardless of the outcome.…”
Section: Pjmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that when employees experience job satisfaction they would also be more committed towards the organisation (affective commitment) (Qureshi, Frank, Lambert, Klahm & Smith 2017). Ensuring that employees are satisfied with both intrinsic (autonomy, skills utilisations) and extrinsic factors (pay, benefits, and working conditions) would increase their psychological identification with the organisation -wanting to work towards the goals of the organisation.…”
Section: Organisational Commitmentmentioning
confidence: 99%